PENDIDIKAN AGAMA ISLAM BERBASIS KAHOOT UNTUK MENINGKATKAN KEAKTIFAN BELAJAR - Khairunnisa Dwi Maulidhina; Purwidianto Purwidianto (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of Kahoot-based Islamic Education learning in improving students’ learning activities at SMA Muhammadiyah 4 Jakarta. The research employed a descriptive qualitative approach to explore the planning, implementation, and evaluation of Kahoot usage in Islamic Education learning. Data were collected through semi structured interviews involving one Islamic Education teacher and four tenth-grade students from different classes, selected using purposive sampling. The collected data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, supported by triangulation to ensure data credibility. The findings indicate that Kahoot is not only used as an evaluation tool but also serves as an effective pedagogical strategy to enhance students’ activeness, focus, motivation, and participation during learning activities. The interactive features, time limits, and competitive elements embedded in Kahoot create an engaging learning atmosphere and encourage students to respond actively. In the context of Al-Islam education in Muhammadiyah schools, the use of Kahoot supports the internalization of Islamic values through contextual and adaptive learning strategies. Therefore, Kahoot can be considered an innovative digital learning medium that contributes positively to increasing students’ learning activities in Islamic Education.